Design, manufacturing, and testing of a prototype green hydrogen production plant based on water electrolysis and solar energy - Mas, R.; Quispe, L.; Pichilingue, D.; Antoniou, A.; Berastain, A.; Chirinos, L.; Celis, C.; Papageorgiou, G. (Elsevier, 2025)
This paper describes the development of a prototype plant for green hydrogen production based on water electrolysis using solar radiation. The development of the prototype plant included several distinct stages. First, the state-of-the-art knowledge regarding the generation of green hydrogen using plant prototypes was established. Next, the hydrogen production system was properly sized, including the required photovoltaic system. Then, the designed green hydrogen production plant (GHPP) prototype was manufactured, assembled, and tested under various operating conditions to assess the feasibility of producing clean energy in an efficient manner. Finally, based on two types of coupling between photovoltaic (PV) and electrolytic (EL) systems, direct and indirect, the developed GHPP prototype was used to effectively generate green hydrogen. The GHPP designed was used to test Proton Exchange Membrane (PEM) electrolyzers. The experimental results obtained here show that some operating conditions, such as the distance between the photovoltaic generation system and the electrolyzer stack, significantly influence the overall efficiency of the developed GHPP. Overall, the findings of this work highlight the need to optimize systems for increasing green hydrogen production and reducing system operating costs.
Keywords: PEM Electrolysis; Renewable Energy Intermittency; https://purl.org/pe-repo/ocde/ford#2.05.05